The supraglottic airway device as first line of management in anticipated difficult mask ventilation in the morbidly obese - Aparna Sinha; Lakshmi Jayaraman; Dinesh Punhani (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Supraglottic airway devices (SGAs) are used to rescue difficult and failed mask ventilation (DMV). We aimed to use the SGA as first-line device, prior to obtaining a definitive airway and to find any predictors of difficulty for the same, in the morbidly obese patients. Material and Methods: Obese surgical patients [body mass index (BMI) >35 kg/m2] were investigated. Difficulties with bag mask ventilation (MV) was graded using the following scale: MV-1, one anesthesiologist unassisted could achieve MV and maintain SpO2 >90%; MV-2, one additional anesthesiologist was needed to facilitate MV to achieve SpO2> 90%; MV-3, two additional anesthesiologists were needed for this purpose; and MV-3P, when a supraglottic device was required to ventilate and maintain SpO2more than 90%. Parameters studied were age, gender, neck circumference (NC), BMI, STOPBANG score, and safe apnea time (SAT). Results: Logistic regression was performed for predictors of MV-3P; receiver operating characteristic curve was used to locate the best cut-off. Analysis of 834 morbidly obese patients revealed an incidence of MV 1/2/3/3-P as 16%/38%/27%/19%, respectively. DMV was associated with BMI ≥50 kg/m2, NC ≥49.5 cm, and STOPBANG ≥6; P < 0.001. The mean SAT for a population with mean BMI 48 ± 8 kg/m2 was 256 ± 66 s. The SAT showed inverse relation to BMI and NC. As per our results, the NC was the single most important predictor of MV-3P, with sensitivity 0.62 and specificity 0.85 at best cut-off 49.5 cm; P < 0.001. Conclusion: NC ≥49.5 cm is strongly associated with low SAT and need for SGA to achieve MV. SGA may provide safety for initial management following induction of anesthesia in this patient population.